TEBASAN PADA USAHA TANI CENGKEH DI DESA MADENAN, KECAMATAN TEJAKULA - I Gusti Agung Semaranata; Gede Mekse Korri Arisena (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research aims to examine three problem factors—first, the characteristics of the tebasan operating in Madenan Village. The second relates to the decision-making basis for determining the value of the penebas. The last is business management. The types and sources of data used were primary and secondary. Respondents in this study were 13 redeemers operating in Madenan Village. Data analysis was used to determine the characteristics, and decision-making basis. Business management used qualitative descriptive analysis, and in determining the decision-making basis for determining the value of the penebas, a Guttman scale was used to get a firm answer. The results showed that the characteristics of penebas in Madenan Village based on age are in the productive age category, which impacts performance and productivity. Based on decision-making, experience plays an important role in the calculation of the interpretation of the penebas that will determine the accuracy of the penebas intuition. In business management, employee monitoring plays an important role in determining the suitability of the interpretation results to reality.